SCHOLARLY TEXT WRITING WORKSHOP: THE INVESTIGATION OF METACOGNITIVE KNOWLEDGE AND ITS IMPACT ON WRITING ARTICLE - Dina Ramadhanti; Lira Hayu Afdetis Mana (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
ABSTRACTWriting research articles has become an absolute obligation for lecturers, researchers, and students to publish their research results. A total of 21 participants attended a scientific article writing workshop and attended an article writing coaching clinic. In addition, a survey was conducted to determine the metacognitive knowledge of the workshop participants in writing articles. An in-depth analysis of the workshop participants' articles shows the effect of metacognitive knowledge in writing articles. The results of the analysis of the metacognitive knowledge questionnaire showed that the metacognitive knowledge of the workshop participants was high. However, this needs to be supported by frequent practice in writing. To develop metacognitive knowledge in writing articles, several solutions are given, namely: being able to plan writing well and systematically, making small notes when understanding the sources read to facilitate paraphrasing and quotations, and using certain applications to facilitate citations and writing references for avoiding plagiarism. In addition, writing articles continuously and publishing them helps the development of metacognitive knowledge in writing scientific articles.Keywords: scholarly text, workshop, metacognitive knowledge, writing